Comprehensive safety assessment of a human inactivated diploid enterovirus 71 vaccine based on a phase III clinical trial. Issue 4 (2nd April 2016) - Zhang, Wei; Kong, Yujia; Jiang, Zhiwei; Li, Chanjuan; Wang, Ling; Xia, Jielai
Abstract: Human enterovirus 71 (EV71) is a causative agent of hand, foot, and mouth disease (HFMD). In a previous phase III trial in children, a human diploid cell-based inactivated EV71 vaccine elicited EV71 specific immune responses and protection against EV71 associated HFMD. This study aimed to assess the factors influencing the severity of adverse events observed in this previous trial. This was a randomized, double-blinded, placebo-controlled, phase III clinical trial of a human diploid vaccine carried out in 12, 000 children in Guangxi Zhuang Autonomous Region, China (ClinicalTrials.gov: NCT01569581). Solicited events were recorded for 7 days and unsolicited events were reported for 28 days after each injection. Age trend analysis of adverse reaction was conducted in each treatment group. Multiple logistic regression models were built to identify factors influencing the severity of adverse reactions. Fewer solicited adverse reactions were observed in older participants within the first 7 days after vaccination ( P < 0.0001), except local pain and pruritus. More severe adverse reactions were observed after the initial injection than after the booster injection. Serious cold or respiratory tract infections (RTI) were observed more often in children aged 6–36 months than in older children. Only the severity of local swelling was associated with body mass index. Children with throat discomfort before injection had a higher risk of serious cold or RTI. These results indicated that the human diploid cell-based vaccine achieved a satisfactory safety profile.